Determination of phenolic compounds and antioxidant activity of green, black and white teas of Camellia sinensis (L.) Kuntze, Theaceae - V.P Pereira; F.J Knor; J.C.R Vellosa; F.L Beltrame (Universidade Estadual Paulista, 2014)
Green, black and white teas are all produced from leaves and shoots of Camellia sinensis, the only difference is how they are processed. The aim of this study was to compare the total phenols and flavonoid contents and antioxidant capacity of green, black and white tea bags of different brands. The morphodiagnosis of leaves was used to identification of plant material. HPLC-DAD fingerprinting coupled with Principal Component Analysis (PCA) was applied to analyze similarities of the tea samples. The results showed considerable variability between tea brands in both total phenols (30.55 to 60.85 mg of pyrogallol/g) and flavonoids (6.35 to 8.92 mg of quercetin/g). Green and white teas demonstrated the highest ABTS and DPPH radical scavenging activities.